Soil drought sets site specific limits to stem radial growth and sap flow of Douglas-fir across Germany - Niessner, Armin; Ehekircher, Stefan; Zimmermann, Reiner; Horna, Viviana; Reichle, Daniel; Land, Alexander; Spangenberg, Göran; Hein, Sebastian (Frontiers in Plant Science, 2024)
Soil drought during summer in Central Europe has become more frequent and severe over the last decades. European forests are suffering increasing damage, particularly Norway spruce. Douglas-fir (Pseudotsuga menziesii (Mirbel) Franco), a non-native tree species, is considered as a promising alternative to build drought-resilient forests. The main goal of this study was to investigate the intraannual radial stem growth and sap flow performance of Douglas-fir along a precipitation gradient across Germany under severe drought. Sap flow and stem radial changes of up to ten trees each at four sites with different precipitation regimes were measured in combination with volumetric soil water content during the growing season of 2022. Measurements of stem radial changes were used to calculate the trees' stem water deficit, a proxy for tree water status and drought stress.The severe summer drought of 2022 led to an early growth cessation and a significant reduction in daily sap flow at all four sites monitored. We could identify a site-specific threshold in soil water availability ranging between 21.7 and 29.6% of relative extractable water (REW) under which stem water reserves can not be replenished and thereby inhibiting radial growth. We could also demonstrate that at this threshold, sap flow is heavily reduced to between 43.5 and 53.3% and for a REW below 50%, sap flow linearly decreases by 1.1-2.0% per 1% reduction in REW. This reduction tends to follow the humidity gradient, being more pronounced at the most oceanic characterized site and suggesting an adaptation to site conditions.Even though Douglas-fir is considered to be more drought stress resistant than Norway spruce, growth and sap flow are greatly reduced by severe summer drought, which became more frequent in recent years and their frequency and intensity is likely to increase. Our results suggest that 1 Niessner et al.timber production of Douglas-fir in Central Europe will decline considerably under projected climate change, and thus pointing to site specific growth constraints for a so far promising non-native tree species in Europe.